PENGARUH KONSERVATISME AKUNTANSI DAN MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Wahyuningsih, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze the influence of accounting conservatism and corporate governancemechanism (management ownership, institutional ownership, independent commissioner, and audit committee)to the firm value. Firm value is the dependent variable in this research that is assessed by Tobinâs Q value. Theindependent variables in this research are accounting conservatism and corporate governance mechanism(management ownership, institutional ownership, independent commissioner, and audit committee). Thesamples are manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2012periods. The data is secondary data which is in the form of annual report and financial statement ofmanufacturing companies that have been published. The data analysis technique is carried out by usingdescriptive statistics test, classic assumption test, and hypothesis test that is done by using multiple linearregressions. The result of this research shows that: (a) accounting conservatism and audit committee has positiveinfluence to the firm value; (b) management stock ownership and institutional stock ownership has negativeinfluence to the firm value, and (c) independent commissioner does not have any influence to the firm value.Keywords: Accounting Conservatism, Management Ownership, Institutional Ownership, IndependentCommissioner, and Audit Committee